DEVELOPMENT OF ENTREPRENEURSHIP: THE EXPERIENCE OF JAPAN - Muazzamxon Mirjalil qizi, Mirjalolova; Alojonovich, Rashidov Rahmatullo (PT. Antis International Publisher, 2025)
Objective: This study examines the Japanese experience in fostering entrepreneurship, with a specific emphasis on the development of small and medium-sized enterprises (SMEs) through institutional support, innovation ecosystems, and favorable financial and fiscal policies. Method: The research employs a qualitative comparative analysis of Japan’s entrepreneurship development framework, highlighting key mechanisms such as public-private partnerships, targeted financing, and legislative strategies. Results: Findings reveal that Japan’s comprehensive support for SMEs has significantly contributed to economic diversification, employment generation, and export growth. The study further translates these insights into actionable recommendations for Uzbekistan, including expanding access to long-term credit, introducing enhanced fiscal incentives, promoting startup incubation, and integrating entrepreneurship education into the national curriculum. Novelty: The article presents a contextualized adaptation of Japan’s integrated entrepreneurial model for Uzbekistan, offering a strategic framework to stimulate innovation-driven growth and competitiveness. This cross-national analysis contributes to the discourse on institutional entrepreneurship support in emerging economies.